Pediatric Zygomaticomaxillary Complex Fracture Repair: Location and Number of Fixation Sites in Growing Children. Issue 1 (July 2018) - Luck, J. D.; Lopez, Joseph; Faateh, Muhammad; Macmillan, Alexandra; Yang, Robin; Davidson, Edward H.; Nam, Arthur J.; Grant, Michael P.; Tufaro, Anthony P.; Redett, Richard J.; Manson, Paul N.; Dorafshar, Amir H.
Abstract : Background: Relatively few reports have been published investigating the operative management of pediatric zygomaticomaxillary complex fractures. The purpose of this study was to assess pediatric zygomaticomaxillary complex fracture management and associated complications, and potentially describe a standard treatment paradigm for these cases. Methods: A retrospective cohort review was performed of all patients younger than 15 years presenting to a single institution with zygomaticomaxillary complex fractures from 1990 to 2010. Patient demographics, concomitant injuries, management details, and complications were recorded. Complications were compared among patients by dentition stage, number of fixation points, and identity of fixation sites. Results: A total of 36 patients with 44 unique zygomaticomaxillary complex fractures met the authors' inclusion criteria. Thirty-two fractures exhibited at least 2.0 mm of diastasis along at least one buttress (73 percent), and all but one of these were managed operatively. Among operatively managed patients with deciduous dentition, two-point fixation was associated with a lower overall complication rate compared with one- and three-point fixation (0 percent versus 75 percent and 75 percent; p = 0.01). Furthermore, rigid plate-and-screw fixation at the zygomaticomaxillary buttress was not associated with an increased complication rate in operatively managed patients with deciduous dentition (40 percent versus 50 percent; p = 0.76). Conclusions: The authors' results suggest that two-point fixation is an effective management strategy for repair of displaced zygomaticomaxillary complex fractures in children. In addition, rigid plate-and-screw fixation at the zygomaticomaxillary buttress in children with deciduous dentition appears to be safe and effective when performed. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.